1995
DOI: 10.1016/s0022-5347(01)67212-4
|View full text |Cite
|
Sign up to set email alerts
|

Incontinence after Radical Prostatectomy: Detrusor or Sphincter Causes

Abstract: Decreased compliance is an infrequent finding after radical prostatectomy. Detrusor abnormalities in general are rarely the sole cause of incontinence, with sphincter weakness being present in the majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
1
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(82 citation statements)
references
References 17 publications
3
76
1
2
Order By: Relevance
“…1 For example, a significant proportion of post-RP patients use abdominal voiding (AV) to empty their bladder. [2][3][4] Abdominal straining during voiding may indicate detrusor underactivity (DU). 3 This is important because DU might affect the efficacy of various surgical treatments for male stress urinary incontinence (UI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 For example, a significant proportion of post-RP patients use abdominal voiding (AV) to empty their bladder. [2][3][4] Abdominal straining during voiding may indicate detrusor underactivity (DU). 3 This is important because DU might affect the efficacy of various surgical treatments for male stress urinary incontinence (UI).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Abdominal straining during voiding may indicate detrusor underactivity (DU). 3 This is important because DU might affect the efficacy of various surgical treatments for male stress urinary incontinence (UI). 5 The International Continence Society (ICS) defines DU as "contraction of reduced strength and/or duration resulting in prolonged bladder emptying and/or failure to achieve complete bladder emptying within a normal time span."…”
Section: Introductionmentioning
confidence: 99%
“…Later, collagen was the better understood and the surgical techniques more sophisticated, the frequency of incontinence has most widely used injection material; recently Aboseif et al [13] reported 47% of patients cured and 19% decreased [1,4,5,6]. Reported incontinence rates after RP range from 1 to 30% [3][4][5][6][7][8][9]. Of 380 patients who showing marked improvement.…”
Section: Resultsmentioning
confidence: 99%
“…However, the most significant complication is post-operative inconattempts to treat incontinence using paraBn injections [20]. PTFE (Polytef ) was first used in a large series about tinence, which aCects up to 30% [5][6][7][8][9]. While low-grade post-operative stress incontinence occurs in nearly 30 years ago [10], but the safety was dubious as the migration of PTFE particles was reported in animal all patients and resolves within 6-12 months [8], high-grade persistent incontinence requires specific studies [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The reported rate of stress incontinence in males after transurethral resection of prostate is 1-5%, 4 and after radical retropubic prostatectomy is approximately 30%. 5,6 There are no figures available for the incidence of male stress incontinence after spinal cord injury (SCI). More than 80% of SCI are in males and two-thirds of these are in individuals less than 30 years of age.…”
Section: Introductionmentioning
confidence: 99%